Systematic status and relationships of Liolaemus species of the archeforus and kingii groups : A morphological and taxonumerical approach (Reptilia: Tropiduridae) - Scolaro, José Alejandro (1997)
A general survey of the several species of the archeforus and kingii groups of the genus Liolaemus was carried out. Liolaemus tristis is described as a new species of the kingii group, and L. tari and L. escarchadosi as new species of the archeforus group. Discriminant analyses have been made to support the real taxonomic status of the new forms. General considerations on their conditions of evolutionary species in the tropidurid Liolaeminae branch were presented.